Attribute Relational Analysis (ARA) for Coherent Association Rules: A post mining process for Parallel Edge Projection and Pruning (PEPP) Based Sequence Graph protrude approach for Closed Itemset (Global Journals of Research in Engineering, 2011)
Association rules present one of the most impressive techniques for the analysis of attribute associations in a given dataset related to applications related to retail bioinformatics and sociology In the area of data mining the importance of the rule management in associating rule mining is rapidly growing Usually If datasets are large the induced rules are large in volume The density of the rule volume leads to the obtained knowledge hard to be understood and analyze One better way of minimizing the rule set size is eliminating redundant rules from rule base Many efforts have been made and various competent and excellent algorithms have been proposed But all of these models relying either on closed itemset mining or expert s evaluation None of these models are proven best in all data set contexts Closed itemset model is missing adaptability and expert s evaluation process is resulting different significance for same rule under different expert s view To overcome these limits here we proposed a post mining process called ARA as an extension to our earlier proposed closed itemset mining algorithm called PEPP
Keywords: post mining; association rule mining; closed itemset; PEPP; Inference analysis; rule pruning